2D (< 10 nm) sp3-C-rich carbon materials, possibly hydrogenated: A review. (October 2022) - Piazza, Fabrice; Monthioux, Marc; Puech, Pascal
Highlights: The main advances on the synthesis of sub-10 nm thick sp 3 -C-rich films are reviewed. Amorphous carbon hydrogenated or not, nanocrystalline diamond films, graphane, diamanes and diamanoids are considered. Physical properties and applications ( i.e. existing or potential) are also highlighted. Abstract: While graphene has held the center stage in nanocarbon material research since its isolation in 2004, less attention has been paid to nanometer-thick carbon films in which at least part of the carbon atoms are sp 3 -hybridized, whatever the crystallographic structure. However, because of their composition, structure, physical and chemical properties, those nanomaterials exhibit competitive features that should be considered for the development of future sustainable technologies based on 2D materials. The purpose of this review is to provide a snapshot of the main advances in the synthesis of sub-10 nm thick sp 3 -C-rich films, which include amorphous carbon hydrogenated or not, nanocrystalline diamond films, graphane, diamanes and diamanoids. Physical properties and applications ( i.e. existing or potential) are also highlighted. Graphical abstract: Image, graphical abstract .